2013
DOI: 10.4274/tjh.2011.0048
|View full text |Cite
|
Sign up to set email alerts
|

Screening Bleeding Disorders in Adolescents and Young Women with Menorrhagia

Abstract: Objective: Chronic menorrhagia causes anemia and impairment of life quality. In this study the aim was the screening of bleeding disorders in adolescents and young women with menorrhagia. Materials and Methods: The study was performed prospectively by pediatric hematologists. A form including demographic characteristics of the patients, bleedings other than menorrhagia, familial bleeding history, characteristics of the menorrhagia, and impairment of life quality due to menorrhagia was filled out by the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
4
15
0
1
Order By: Relevance
“…These studies mostly involve retrospective chart reviews of inpatients with acute menorrhagia or referrals to hemophilia treatment centers. Data on the frequency and etiology of menorrhagia in university students are scarce, despite gynecological complaints are common in this age group [21][22][23]. The pictorial blood-loss assessment chart (PBAC) is a practical and objective method that has a high sensitivity and specificity when >100 score is accepted to define menorrhagia [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These studies mostly involve retrospective chart reviews of inpatients with acute menorrhagia or referrals to hemophilia treatment centers. Data on the frequency and etiology of menorrhagia in university students are scarce, despite gynecological complaints are common in this age group [21][22][23]. The pictorial blood-loss assessment chart (PBAC) is a practical and objective method that has a high sensitivity and specificity when >100 score is accepted to define menorrhagia [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…There is now a better understanding of its pathophysiology. [1][2][3][4] There is more precise terminology 5 and an improved classification system. 6,7 New, effective medical therapies [8][9][10][11] and less invasive surgical treatment options have also become available.…”
mentioning
confidence: 98%
“…Studies have reported that the frequency of coagulation disorders in adolescent and adult women with increased and irregular menstrual bleeding is between 17% and 50%, and von Willebrand disease is the most common among these disorders. [14][15][16] The relationship between increased menstrual bleeding and von Willebrand has been well known for a long time. However, it may be overlooked when the patient does not give a good history.…”
Section: Discussionmentioning
confidence: 99%